PENGGUNAAN MEDIA HONOR ( POHON NORMA ) PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS 4 SD PADA HASIL BELAJAR SISWA - Izza Nugraha, Jihan; Zuni Eka Tiyas Rifayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the use of HONOR media (Norm Tree) in Civics Education learning and its impact on the learning outcomes of fourth-grade elementary school students. The research employed a qualitative approach with a descriptive design. The research subjects consisted of one teacher and thirteen fourth-grade students at SDI Al-Hikmah. Data were collected through observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results indicate that the use of HONOR media increases students’ activeness, attention, and engagement in the learning process. Students were able to understand the concept of norms and their application in daily life more easily. In addition, the learning atmosphere became more interactive and enjoyable. Therefore, HONOR media (Norm Tree) is effective as a learning medium in Civics Education to improve the learning outcomes of fourth-grade elementary school students.